A case of unusual presentation of acute esophageal necrosis with pneumonia - Melki, Gabriel; Nanavati, Sushant; Kumar, Vinod; Komal, FNU; Mohamed, Abdalla; Mohamed, Hadir; Karim, Gres; Laham, Linda; Kuru, Sugabramya; Botros, Youssef; Grossman, Matthew; Michael, Patrick (International Journal of Health Sciences, 2020)
Acute esophageal necrosis (AEN) is a rare and often fatal pathology of unclear etiology affecting the distal two-thirds of the esophagus. Typically, elderly patients with multiple comorbidities present with signs of upper gastrointestinal (GI) hemorrhage. On endoscopy, the mucosa is black due to ischemic necrosis, resulting in the commonly used term “black esophagus.” We present a rare case of a 61-year-old male presenting with shortness of breath and hematemesis diagnosed as AEN through endoscopy. This case illustrates the importance of considering AEN as part of differential diagnoses in a rising elderly population with multiple comorbidities that present with upper GI hemorrhage. Treatment should be aimed at maintaining hemodynamic stability with high-dose proton pump inhibitors.